(untitled) (Social Science Review, 2023)
The objective of this research is to find out the relationship between Rohingya minorities of Myanmar and black communities in the USA from the lens of systemic racism. The Rohingya have been tortured for their ethnic identity just as the black communities are being persecuted outside of Asia. The black movement of America increase on May 25, 2020, in the midst of the COVID-19 pandemic when black man George Floyd died by the physical torture of policemen. In the same way, the Rohingya people saw various military armed insurrections in their whole lifetime yielding unlimited pain and unacceptable experience for the community. From the 1940s, they have been persecuted by their own government till the huge influx in 2017 which forced the majority to take shelter in Cox’s Bazar, Bangladesh. More than 1 million Rohingya people are now living in these largest camps for displaced persons in the world. Despite the growing systemic racism in these two communities in the two parts of the world, few literatures focused on the co-relations between them and hardly defined these crises from the systemic racism lens. We largely based our arguments on the challenges of practicing Rohingya culture based on secondary source analysis. However, the research finds comparative analysis between the Asian communities has become an urgent need for further research. Social Science Review, Vol. 39(1), June 2022 Page 75-90